Emitter Localization Algorithm Based on Passive Synthetic Aperture - Zhang, Liting; Huan, Hao; Tao, Ran; Wang, Yue (IEEE transactions on aerospace and electronic systems, 2022)
Emitter localization is an active research topic in electronic reconnaissance. Recently, passive synthetic aperture (PSA) has been used to determine the azimuth and range distance of the emitter. However, the existing methods approximate the distance equation of the spaceborne model through the airborne model, resulting in a large positioning error. In this article, an emitter localization algorithm based on PSA in the spaceborne model is proposed. First, the phase of the received signal is accumulated by using the symmetry of the Doppler history of the received signal in long synthetic aperture time, improving the azimuth positioning accuracy. The effective velocity is then used to establish the nonlinear equations of range distance. A modulus function is used to solve the equations, correcting the range positioning error in the spaceborne model. Finally, the influence of noise, satellite position error, and satellite speed error on the positioning results is analyzed. The error matrix of the proposed method in wide swath is obtained. Simulation results show that the positioning accuracy of this method is one order of magnitude higher than that of traditional single-satellite positioning methods. The effectiveness of the proposed method is verified through actual satellite experiments.